Ocular Structural and Vascular Changes in Patients with Severe Asymptomatic Carotid Disease After Undergoing Carotid Endarterectomy (CEA) and Carotid Artery Stenting (CAS) - Foteini Xanthou; Anna Dastiridou; Athanasios Giannoukas; Miltiadis Matsagkas; Chara Tzavara; Athanasios Chaidoulis; Sofia Androudi; Evangelia E. Tsironi (Diagnostics)
Background/Objectives: This study aimed to prospectively assess the incidence of retinal embolization and to evaluate the vascular and structural changes in the retina and choroid in 52 patients with asymptomatic severe carotid artery disease who underwent carotid artery revascularization. Methods: In our study, 35 patients underwent carotid endarterectomy (CEA) and 17 underwent carotid artery stenting (CAS). Biomicroscopy, fundoscopy, optical coherence tomography (OCT), and OCT-angiography (OCTA) were performed at baseline and 1 month after revascularization. Results: The subfoveal choroidal thickness (SFCT), peripapillary choroidal thickness inferior to the optic nerve head (ppCTi), total overall average retinal vascular density (rVDtot), and total overall average choriocapillaris vascular density (ccVDtot) of the eyes ipsilateral to the operated carotid artery increased significantly after revascularization, whereas a statistically significant increase was also found in the SFCT, rVDtot, and ccVDtot of the contralateral eyes in the overall cohort. Comparing the two study groups, we found that the SFCT, superior and inferior peripapillary choroidal thicknesses (ppCTs, ppCTi), rVDtot, and ccVDtot increased in both groups after revascularization, but significantly only in the CEA group. Furthermore, the temporal choriocapillaris vascular density (ccVDt) increased significantly after revascularization in both groups to a similar degree. Conclusions: Carotid artery revascularization led to a statistically significant increase in retinal and choroidal vascular densities, which indicates significantly improved ocular perfusion. The analysis of the findings of the two study groups suggests the superiority of CEA in terms of improving ocular perfusion in asymptomatic severe carotid artery disease. The rate of retinal embolization was similar in both surgical groups.